2013
DOI: 10.1002/sia.5309
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of copper nanoparticles surface‐capped by alkanethiols

Abstract: Cu nanoparticles surface‐capped by alkanethiols were synthesized using ligand exchange method in a two‐phase system. The effects of synthetic conditions, including the pH value of CuSO4 solution, the ratio of cetyltrimethyl ammonium bromide to CuSO4, and reaction temperature, on the size and shape of as‐synthesized Cu nanoparticles were investigated. As‐synthesized Cu nanoparticles surface‐capped by alkanethiols with different chain lengths (CxS‐Cu) were characterized by means of X‐ray diffraction, transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Many methods have been reported for the synthesis of Ag and Cu NPs such as chemical reduction routes and polyol process . Metal NPs ranging from one to several hundred nanometers in diameter can be obtained by tuning the molecular cross section of surfactant molecules . The fabricated metal NPs can then be dispersed in various solvents such as glycerol, ethanol, dodecane, acetone, toluene, and butylbenzene to form stable ink (Figure g,h) .…”
Section: Ink Formulationmentioning
confidence: 99%
“…Many methods have been reported for the synthesis of Ag and Cu NPs such as chemical reduction routes and polyol process . Metal NPs ranging from one to several hundred nanometers in diameter can be obtained by tuning the molecular cross section of surfactant molecules . The fabricated metal NPs can then be dispersed in various solvents such as glycerol, ethanol, dodecane, acetone, toluene, and butylbenzene to form stable ink (Figure g,h) .…”
Section: Ink Formulationmentioning
confidence: 99%
“…Form here the metallic NPs have a small particle size, high surface area, low melting point, and low shear strength. They provide excellent tribological performance and self-repairing function as lubricant additives [39], including Cu, Bi, Sn, Fe, Ni, Al, Pd, Co, Zn. The lubrication mechanism of metallic NPs can be categorized into (a) the surface properties will be changed and separate two friction surfaces with the formation of tribofilms, hence provide promising tribological performance; (b) NPs roll between two friction surface leading to the reduction of friction and wear; (c) heat and pressure generated during operation, leading to the compaction of NPs on the wear track, with this phenomenon considered as a repair or sintering effect [38].…”
Section: Metalmentioning
confidence: 99%
“…The addition of nano-bismuth in light and heavy base oil resulted in wear reduction from 535 to 454 µm and 651 to 563 µm, friction reduction from 0.091 to 0.052 and 0.074 to 0.047 [42]. The addition of nanoCu in paraffin oil resulted in a reduction of friction (23%) and wear (26%) [39]. An investigation of the tribological properties of nanoNi in PAO6 reported a reduction of 7-30% in wear and 5-45% in friction [43].…”
Section: Metalmentioning
confidence: 99%
“…Yang et al found that the base oil with g-C 3 N 4 /Cu exhibited excellent lubricating behaviors with lower friction coefficient and wear rate, which may be due to the synergistic lubrication effect of g-C 3 N 4 and Cu NPs on the interface (Yang et al, 2015). Our group reported that alkanethiols-capped Cu NPs in liquid paraffin possessed excellent tribological properties (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 74%